Comparison Of Ethanol Emulgel Extract Activity Of Duku Fruit Peels (Lansium domesticum Corr) With Tranexamic Acid As A Skin Lightener - Lusi Nurdianti (Journal of Global Pharma Technology, 2020)
ABSTRACT Objective : Emulgel which has the potential for skin lightener is a medical cosmetic preparation used to inhibit the formation of melanin pigments so that it can brighten the skin. The purpose of this study was to determine the effect of concentration variations of duku (Lansium domesticum Corr.) peel waste extracts on the evaluation results of preparations, the level of irritation to rabbits, and an increase in brightness on human skin compared with emulgel containing tranexamic acid. A dermatoscopic test is used to look at the imaging of the skin surface after the use of an emulgel. Material and Method : In this study, concentration variations of ethanol extract from duku peel waste of 10%, 15% and 20% were used. Result : The test results obtained that all formulas meet the requirements of organoleptic test, pH, homogeneity, dispersibility, and centrifugation test. Irritation test with the Draize method obtained all formulas do not irritate. The results of testing the increase in skin brightness on emulgel preparations showed that F1 (16.67%), F2 (33.33%), F3 (60%), F4 (60%). Conclusion : Increasing the brightness of emulgel preparations containing 20% ethanol extract of duku peel is comparable to 4% tranexamic acid.Keywords: Tyrosinase, Lightening cream, Duku fruit Peel, Tranexamic acid.